Innovating Halal Assurance in Individual Broiler Chicken Slaughterhouses: A Model for Ethical and Decentralized Meat Processing - Lusianti, Dina; Yasin, Rozaq Muhammad; 'Ula, Ahmad Nilnal Munachifdlil (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
Chicken is the most widely consumed source of animal protein in Indonesia. However, individual broiler chicken slaughter practices often prioritize consumer satisfaction and high consumption over halal compliance and health standards. This study highlights a critical gap in halal assurance, particularly within informal or individual slaughtering systems, which are often overlooked in previous research that focuses on large-scale or mechanized slaughterhouses for cattle. This research aims to develop a business model and standard operating procedure (SOP) for halal assurance management specifically tailored to individual broiler chicken slaughterhouses. Using a mixed-methods approach, the study engages stakeholders including slaughterhouse communities, the Ministry of Religious Affairs, the Animal Husbandry Service, Islamic Higher Education (Halal Study Centers), and Islamic law experts. The findings contribute to the formulation of practical guidelines for ensuring halal, safe, healthy, and high-quality (ASUH) chicken products. Globally, this study addresses the increasing demand for ethical and religiously compliant food systems, offering a model that integrates halal principles into decentralized meat processing. Its implications support consumer protection, supply chain transparency, and the promotion of ethical food practices in both Muslim-majority and international markets concerned with halal certification and food integrity.